2006
DOI: 10.1074/jbc.m601777200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis and Insights into the Reduced Toxicity of Abrus precatorius Agglutinin I in Relation to Abrin

Abstract: Abrin and agglutinin-I from the seeds of Abrus precatorius are type II ribosome-inactivating proteins that inhibit protein synthesis in eukaryotic cells. The two toxins share a high degree of sequence similarity; however, agglutinin-I is weaker in its activity. We compared the kinetics of protein synthesis inhibition by abrin and agglutinin-I in two different cell lines and found that ϳ200 -2000-fold higher concentration of agglutinin-I is needed for the same degree of inhibition. Like abrin, agglutinin-I also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 55 publications
(53 reference statements)
4
59
0
Order By: Relevance
“…Studies to determine the reactivity of mAb A7C4 to the RIPs abrin and APA demonstrated that in spite of 67% sequence identity between ABA and APAA, 16 the core epitope of mAb A7C4 is restricted to amino acid sequence unique to abrin A chain within 1-123 amino acids. Moreover, mAb A7C4 did not bind to the chimeric construct ABA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to determine the reactivity of mAb A7C4 to the RIPs abrin and APA demonstrated that in spite of 67% sequence identity between ABA and APAA, 16 the core epitope of mAb A7C4 is restricted to amino acid sequence unique to abrin A chain within 1-123 amino acids. Moreover, mAb A7C4 did not bind to the chimeric construct ABA …”
Section: Discussionmentioning
confidence: 99%
“…Though ABA and APAA share 67% sequence identity, 16 the observation that mAb A7C4 does not recognize the sequence of APAA suggests that the core epitope comprises majorly of the amino acid sequences that are unique to ABA only. The absence of binding to the construct APA 1-123 ABA (Fig.…”
Section: Neutralization Of Abrin-induced Cytotoxicity By Mab A7c4mentioning
confidence: 99%
“…For ricin, the oral toxicity in humans expressed as half-maximal lethal dose (LD50) is estimated to be 1-20 mg/kg body weight and for abrin 0.1-1 mg/kg body weight.3,4 Both R. communis and A. precatorius seeds contain a second toxic lectin named R. communis agglutinin and A. precatorius agglutinin, which are highly homologous (around 90% sequence identity for ricin and R. communis agglutinin) to ricin or abrin, respectively, but are less toxic. [5][6][7] of cholinergic neurons to induce flaccid paralysis by interfering with components of the vesicle fusion machinery. Exceedingly small quantities of toxin are sufficient for poisoning: the oral lethal dose of botulinum toxin for man is approximately 1 mg/kg.8 Staphylococcal enterotoxin B (SEB) is one of several heatstable enterotoxins produced by the Gram-positive bacterium Staphylococcus aureus, which is known as a major human pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of Abrus precatorius L. are among the most poisonous seeds in the world and contain principle compound, abrine, abrin A, abrin B, abrin C abricin and abridin 12 . The present work deals with phytochemical analysis and chemical fingerprinting of important medicinal plant, Abrus precatorius L.…”
Section: Introductionmentioning
confidence: 99%